Determination of Some Trace Metals in Edible Mushrooms Samples Using Atomic Absorption Spectrometry - Turhan, Kadir (SPRINGER, 2009)
Trace metal levels in ten different mushroom species, Lactarius decipiens Quel., Lactarius piperatus, Lactarius resimus Fr, Lactarius valemus Fr, Lactarius vietus (Fr) Fr, Laccaria lacceta, Agaricus bisporus, Agaricus silvicola, Lentinula edodes and Morchella deliciosa obtained from different areas of the middle Black Sea region of Turkey were determined by flame and graphite furnace atomic adsorption spectrometry after microwave digestion. The contents of trace metals in the mushroom samples were found in the ranges 74.21-127.70, 23,444-49,880, 69.51-99.93, 46.23-129.38, 3.69-27.51, 0.71-3.11, 0.41-1.57, 16.35-27.92, 3.54-29.87, 759-1,200, 0.24-1.41, 8.69-22.41 and 0.13-0.54 mu g/g for Na, K, Ca, Fe, Cu, Pb, Cd, Zn, Mn, Mg, Cr, Ni, and Co, respectively. Results obtained are in agreement with trace data reported in the literature.
Keywords: Atomic absorption; Black Sea; mushrooms; trace metals; HEAVY-METALS; ELEMENTS; Biochemistry & Molecular Biology; Chemistry